The Reconstruction of Religious Education Into Community’s Legal Life - Hassan Suryono (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
The aim of this study was to elaborate on how religious education can be implemented to community life as the reference and norm of behavior in their life. Religious education developed in legal order remained to be needed inexplicitly. There is a tendency that the community wanted to organize their life corresponding to the religion. For making the religion to be alive, the state’s leadership and participation is needed to regulate it. The constructed religion value in community behavior manifested in legislation will ensure the presence of both law certainty and law enforcement. Thus, religion and law containing regulations and prohibitions will bind to everyone, either ordinary people or rulers. Religion becoming the universal foundation of life. So,  there should be identification and verification of shared religious values before they are constructed to be law in the plural community life.